Power plant instrumentation and control handbook : a guide to thermal power plants - Basu, Swapan; Debnath, Ajay Kumar (Academic Press, an imprint of Elsevier, 2019)
Power Plant Instrumentation and Control Handbook, Second Edition, provides a contemporary resource on the practical monitoring of power plant operation, with a focus on efficiency, reliability, accuracy, cost and safety. It includes comprehensive listings of operating values and ranges of parameters for temperature, pressure, flow and levels of both conventional thermal power plant and combined/cogen plants, supercritical plants and once-through boilers. It is updated to include tables, charts and figures from advanced plants in operation or pilot stage. Practicing engineers, freshers, advanced students and researchers will benefit from discussions on advanced instrumentation with specific reference to thermal power generation and operations. New topics in this updated edition include plant safety lifecycles and safety integrity levels, advanced ultra-supercritical plants with advanced firing systems and associated auxiliaries, integrated gasification combined cycle (IGCC) and integrated gasification fuel cells (IGFC), advanced control systems, and safety lifecycle and safety integrated systems. --